Relação da Participação Orçamentária, Assimetria da Informação e Compensações com a Folga Orçamentária em um grupo de Empresas Familiares - Souza, Mayk Jonhon de Carvalho (2021)
This study sought to understand the relationship of the variables budgetary participation, information asymmetry and compensation with budgetary slack in a family business in the automobile sector. Therefore, a survey of information was carried out through a survey single entity, and data collection took place through an interview and questionnaire application, whose answers were analyzed using Multiple Regression. The findings showed that the family is present in strategic decision-making, through the occupation of board positions and the family council, which deliberates on budget, financial and investment decisions. It was found that the group has a technical team for preparing the business budget and, based on that, meetings are held with department managers and directors to decide on the final values. It was identified that the group stipulates a spending package and, by not using the entire amount available, managers are evaluated and remunerated based on this savings. It was found, therefore, that the group pays financial and non-financial compensation to managers subject to compliance with budget targets. The study's findings also showed that the budget elaboration structure implies the constitution of budgetary slack, and the participation of managers in the budget elaboration occurs in a moderate way in the researched group. As for information asymmetry, it was identified that managers are more familiar with the activities of their departments and believe they know more about the potential performance of their areas of responsibility in relation to their superiors. The results indicate that there is the possibility of creating a slack in the budget in the researched group, since there is participation of managers in the budget and that they hold more information than their immediate leaders. The findings also show that there is a positive and significant influence of budgetary participation and offsets on budgetary slack, that is, slack is maximized when the level of participation and offsets is high. For asymmetry, no significant result was found in the study sample. It is expected that this study will generate theoretical contributions to the areas of Management Accounting and Controllership, by employing the Stewardship Theory to analyze the budgetary slack in family organizations. This research demonstrates results contrary to those found in the literature on family organizations and on the Stewardship Theory, evidencing a gap between theory and practice and, therefore, the need for additional research on the subject. In terms of practical contributions, it is expected that the results of this study can collaborate with family organizations by identifying the level of budgetary slack and its relationship with the variables researched in the preparation of the budget. It is concluded, therefore, that the findings are, in part, contrary to what is recommended in the literature on family organizations and the Stewardship Theory, which indicates that the interests of the organization and managers would be aligned with the payment of financial and non-financial compensation.